Modified laser beam profiling of He-Ne and diode laser - 362140 Nurfariza Muslin; Yusof Munajat, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Fizik Kesihatan)) - Universiti Teknologi Malaysia, 2007